High-density lipoprotein: relations to metabolic parameters and severity of coronary artery disease. - Tornvall, P; Karpe, F; Proudler, A; Båvenholm, P; Landou, C; Olivecrona, T; Hamsten, A (1996)
The regulation of plasma high-density lipoprotein (HDL) cholesterol level by the joint influence of plasma lipoprotein lipids, lipoprotein lipase (LPL), hepatic lipase (HL), cholesteryl ester transfer protein (CETP), oral glucose tolerance, and postload plasma insulin and proinsulin levels was investigated in young postinfarction patients and healthy population-based control subjects. In addition, the association between HDL cholesterol and the number and severity of coronary stenoses previously reported in this cohort of young postinfarction patients was further investigated by analyzing the determinants and angiographic relations of HDL subclasses measured by gradient gel electrophoresis. The following parameters showed significant univariate relations with HDL cholesterol level in the patient group: very-low-density lipoprotein (VLDL) cholesterol and triglyceride, low-density lipoprotein (LDL) triglyceride, and postload plasma insulin concentrations, preheparin plasma LPL mass, and postheparin plasma HL activity. In the control group, significant correlations with HDL cholesterol concentration in addition to those noted among the patients were found for body mass index (BMI), LDL cholesterol level, postload plasma intact proinsulin concentration, and LPL activity in postheparin plasma. In contrast to the patients, no significant relations were noted for postload plasma insulin level and preheparin plasma LPL mass. Multiple stepwise regression analysis showed that 42% of the variability of HDL cholesterol in the patients could be accounted for by VLDL cholesterol concentration (29%), LDL triglyceride level (7%), and postheparin plasma HL activity (8%), whereas the corresponding figure in controls was 35% (VLDL cholesterol concentration [9%] and postheparin plasma HL activity [26%]. The strength of the relationships of HDL cholesterol and HDL subclasses to the coronary stenosis score was similar and statistically significant (r = .25 to .36). When the metabolic parameters that correlated with HDL cholesterol and HDL subclass concentrations in univariate analysis were used as covariates, all relations to the coronary stenosis score disappeared. This clearly indicates that the influence of triglyceride-rich lipoproteins and lipolytic enzymes needs to be considered when assessing the association between HDL cholesterol and coronary artery disease (CAD).